Belarus Macroeconomic Update : Achieving Stability and Growth - World Bank (World Bank, Washington, DC, 2017)
This note assesses recent macroeconomic developments in Belarus and presents a medium-term economic outlook for 2013-2016 in three scenarios. These scenarios are sensitive to underlying assumptions and are provided to illustrate the main macroeconomic policy choices, available to Belarus. The first scenario (baseline scenario) assumes that the authorities continue macroeconomic policies of the past year, with alternating phases of policy loosening and tightening, motivated by attempts to balance growth and stability. The second scenario (expansionary scenario) assumes that the authorities pursue more aggressive expansionary policies (compared to the baseline scenario) to boost growth in the short term. Prioritizing growth at the expense of stability will reignite macroeconomic imbalances.The third scenario (sustainable growth scenario) assumes that the authorities put in place policies that ensure macroeconomic stability and provide a basis for sustainable growth. This includes a policy framework that (i) maintains the flexible exchange rate regime; (ii) sustains tight monetary policy, namely containing credit growth, including under government directed lending programs to contain inflation and real exchange rate appreciation; (iii) balances wage growth so that it does not exceed productivity growth; (iv) maintains tight fiscal policy and a balanced budget over the medium term. These three scenarios highlight the main macroeconomic trade-offs that Belarus is facing in the current environment. This note is organized as follows: Section one highlights recent macroeconomic trends; Section two provides the three macroeconomic scenarios; and Section three provides the Bank’s recommendations for macroeconomic and structural policies. Annex one outlines the structural modernization agenda that could support sustainable medium term growth. Annex two provides detailed assumptions, underlying the three scenarios. Annex three presents the results of simple sensitivity analysis of the potential impact of price declines in potash fertilizer.